Reconstruction of Over-the-Counter Transaction Settings Based on Legal Certainty - I Wayan Surya Hamijaya J (Jurnal Dinamika Hukum, 2019)
OTC (Over-the-Counter) Transaction has become one of the alternative choices that greatly benefits to the parties. Problems then arise when the law has been formed by the competent authority, but it creates legal uncertainty due to the regulations that regulate the same things but different contents. The OTC Transactions are regulated in Financial Services Authority Regulation Number 22 / POJK.04 / 2019 on Securities Transactions. It is stated that the OTC are included in securities transactions, of which transactions can be done both in the primary and secondary markets. However, the Regulation Number 8 of 1995 does not regulate the OTC transactions. This can lead to the legal uncertainty towards the OTC transaction agents since there are more than one regulation governing the same problem. In addition, a reconstruction is needed for legal protection and dispute resolution related to the OTC transactions.Keywords: OTC transactions, regulatory reconstruction, legal certainty.